2013
DOI: 10.1007/s00467-013-2676-4
|View full text |Cite
|
Sign up to set email alerts
|

Growth of children with end-stage renal disease undergoing daily hemodialysis

Abstract: Our data show that the DHD favored a 0.5 SDS height gain in a third of patients without GH treatment. Dialysis intensification was not a cause for treatment dropouts, and DHD should be considered as a treatment for selected cases, especially small children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 21 publications
0
7
0
2
Order By: Relevance
“…In an observational study on 24 children undergoing daily hemodialysis (DHD) vs 26 children on conventional HD, nearly one ‐third of patients in the DHD group had an increase in the height of 0.5 SDS as opposed to only one‐tenth patients in the control group with similar results. Also, nearly all the patients in the DHD group had an adequate total caloric intake, whereas only 38% in the CHD group had improvement in dietary intake . Fischbach et al reported an increase in growth velocity from 3.8 ± 1.1 to 14.3 ± 3.8 cm/y during the first year in 15 children receiving in‐center daily online hemodiafiltration along with a resultant change in height SDS over the entire duration of follow‐up from −1.5 ± 0.3 SDS to +0.2 ± 1.1 SDS …”
Section: Advantages Of Intensified Hdmentioning
confidence: 99%
See 1 more Smart Citation
“…In an observational study on 24 children undergoing daily hemodialysis (DHD) vs 26 children on conventional HD, nearly one ‐third of patients in the DHD group had an increase in the height of 0.5 SDS as opposed to only one‐tenth patients in the control group with similar results. Also, nearly all the patients in the DHD group had an adequate total caloric intake, whereas only 38% in the CHD group had improvement in dietary intake . Fischbach et al reported an increase in growth velocity from 3.8 ± 1.1 to 14.3 ± 3.8 cm/y during the first year in 15 children receiving in‐center daily online hemodiafiltration along with a resultant change in height SDS over the entire duration of follow‐up from −1.5 ± 0.3 SDS to +0.2 ± 1.1 SDS …”
Section: Advantages Of Intensified Hdmentioning
confidence: 99%
“…15,20,21 Another major concern in children undergoing chronic hemo- had an adequate total caloric intake, whereas only 38% in the CHD group had improvement in dietary intake. 19 Overall intensified dialysis regimens have noteworthy advantages which need to be validated in larger cohorts of patients so that intensified dialysis programs can become a norm rather than an exception.…”
Section: Advantag E S Of Inten S Ified Hdmentioning
confidence: 99%
“…Intensified dialysis programs for children and adolescents have been established in very few centers worldwide [37][38][39][40][41][42][43] (Table 2).…”
Section: Intensified Dialysis Programs For Children and Adolescentsmentioning
confidence: 99%
“…In a second study, the research group showed that SDHD promotes catch-up growth in combination with growth hormone therapy [41], leading these authors to speculate that the improved response to recombinant human growth hormone is the result of less malnutrition and cachexia, De Camargo et al reported on improved growth in children and adolescents on SDHD even without growth hormone therapy. In their prospective, observational study, 33 % of the patients on SDHD showed a 0.5 standard deviation score (SDS) for height gain, whereas only 8 % of the patients on conventional HD achieved the same level [43]. The quality of life in children and adolescents on SDHD is not currently being systematically investigated.…”
Section: Intensified Dialysis Programs For Children and Adolescentsmentioning
confidence: 99%
“…15 To further support the argument for better generalized health with longer treatment time, daily hemodialysis has been associated with improved nutrition and improved growth in children with ESRD. 16 Ikizler argued that the selection of healthier patients to longer treatment time may introduce bias favoring the outcomes of longer treatment time. 17 In the only observational multinational study to date showing higher mortality in patients receiving daily hemodialysis compared with those receiving conventional hemodialysis, the authors speculate that some of the French patients may have been assigned daily hemodialysis as rescue therapy and thus were actually sicker than those who received conventional hemodialysis.…”
Section: Donald Rumsfeld February 2002 Us Department Of Defense Newsmentioning
confidence: 99%